Investing in a Better Future through Public Agricultural Research - Huffman, Wallace; Norton, George; Tweeten, Luther G. (Council for Agricultural Science and Technology (CAST), 2011)
Everyone is concerned with return on investment, and agricultural research continues to be an example of the positive impact well-placed funding can have. Agriculture is a key to the nation’s economy, and research not only boosts that industry, it also promotes solutions for many of the country’s pressing problems in the areas of health, energy, environment, rural development, trade, and food safety. This Commentary is directed to the Congress (for funding), the Administration (for initiatives), and the public (for insight). Recognized scholars provide an assessment of the high “rate of return” agricultural research has delivered to the American and global public and why funding is truly in the public interest. As the authors point out, “Plans for a better future start today.”
Keywords: Public Research; Agriculture; Health; Energy; Environment